1993
DOI: 10.1111/j.1473-4192.1993.tb00041.x
|View full text |Cite
|
Sign up to set email alerts
|

What is applied linguistics?

Abstract: Applied linguistics in one of its manifestations can be defined as that knowledge of language that can be used to influence language performance. Yet it is an ill‐defined and underdefined discipline. Earlier definitions have been of two principal kinds: the ostensive and the expository. These are assessed here. The key to a meaningful definition lies in the dual articulation of applied linguistics: it is an interface between linguistics and practicality. While this interface has traditionally been a human expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Students new to AL and perhaps for those students in the Brazilian context who are in the midst of writing up their theses or dissertations for advanced degrees might be perplexed about the uncertainty of what exactly AL entails based on the writings of a number of founding fathers of the field (WIDDOWSON, 2000a;HASAN;PERRET, 1994;JAMES, 1993). But quite surprisingly, a number of younger researchers still harbor doubts about the scope of AL.…”
Section: Conflicting Definitions Of the Disciplinementioning
confidence: 99%
“…Students new to AL and perhaps for those students in the Brazilian context who are in the midst of writing up their theses or dissertations for advanced degrees might be perplexed about the uncertainty of what exactly AL entails based on the writings of a number of founding fathers of the field (WIDDOWSON, 2000a;HASAN;PERRET, 1994;JAMES, 1993). But quite surprisingly, a number of younger researchers still harbor doubts about the scope of AL.…”
Section: Conflicting Definitions Of the Disciplinementioning
confidence: 99%
“…We see that on the one hand it involves all of the sorts of intervention that we associate with FL teaching: explanation, key sentences, dialogues, passages and teachers' demonstrations -mime and tomfoolery. The second role of DEC is as a data base, reminiscent of the knowledge store learners refer to when monitoring, or, more ambitiously, the knowledge base in an expert system (James, 1993). KJ makes passing reference to expertise.…”
Section: Language Teaching and Skill Learningmentioning
confidence: 99%
“…suggested that contrastive analysis had no predictive power and all L2 errors could be predicted. This has led to some like Kellerman and Sharwood (1986) to talk of 'cross-linguistic influence, and Selinker (1983) of language transfer, and James (1990) preferred to use 'transfer analysis. However, no scholars have doubted that the mother tongue has at least some level of influence on the process of learning the target language.…”
Section: Introductionmentioning
confidence: 99%
“…The learners' prior linguistic knowledge, of one language or many languages, should have its effect on learning the target language. James (1990) explored two potential causes of errors:…”
Section: Introductionmentioning
confidence: 99%